Power, Powerlessness and Addiction / [electronic resource] - Orford, Jim (Cambridge : Cambridge University Press, 2013)
Addiction exercises enormous power over all those who are touched by it. This book argues that power and powerlessness have been neglected in addiction studies and that they are a unifying theme that brings together different areas of research from the field including the disempowering nature of addiction; effects on family, community and the workplace; epidemiological and ethnographic work; studies of the legal and illegal supply; and theories of treatment and change. Examples of alcohol, drug and gambling addiction are used to discuss the evidence that addiction is most disempowering where social resources to resist it are weakest; the ways in which the dominant discourses about addictive behaviour encourage the attributing of responsibility for addiction to individuals and divert attention from the powerful who benefit from addiction; and the ways in which the voices of those whose interests are least well-served by addiction are silenced.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).
Keywords: Compulsive behavior; Control (Psychology)